2017
DOI: 10.1080/21513732.2017.1349836
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem services and biodiversity trends in Mozambique as a consequence of land cover change

Abstract: The incorporation of ecosystem services (ES) information in planning decisions is an important factor in the sustainable use of natural resources. However, studies assessing the levels and changes of these services at national level are rare. In this paper, we estimate past and future changes in multiple ES and biodiversity, as a consequence of land cover change (LCC) in Mozambique. Water yield, water quality, erosion regulation, climate regulation, and biodiversity were modeled using a spatially explicit appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 72 publications
2
19
0
Order By: Relevance
“…Different management alternatives are needed to incorporate scenarios in a science-policy interface for environmental assessments [25]. Thus, the use of plausible scenarios at regional scales may support sustainable development in a context of environmental changes on land systems [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Different management alternatives are needed to incorporate scenarios in a science-policy interface for environmental assessments [25]. Thus, the use of plausible scenarios at regional scales may support sustainable development in a context of environmental changes on land systems [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Land use/cover change (LUCC) is increasingly impacting on the Earth's surface biophysics, biogeochemistry, and biogeography at any rate or scale such as ecosystem services [1][2][3], water balance [4][5][6][7][8], climate [9][10][11][12][13][14], biodiversity conservation [15][16][17], and agriculture [18]. It means land use/cover information is important for natural resources planning and management [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…These provinces are vastly explored for oil, coal, hydrocarbons and minerals 46 , presenting severe challenges for biodiversity conservation. Moreover, the high population growth observed in the northern provinces is associated with agricultural development and habitat degradation 47,48 . Given that habitat loss is a leading cause of biodiversity decline, there is an urgency to study and survey the provinces identified in this study since some economic activities, such as mine-exploration and plantation forestry, without proper impact studies may lead to irreversible biodiversity loss 49,50 .…”
Section: Resultsmentioning
confidence: 99%